2006
DOI: 10.1158/0008-5472.can-06-0383
|View full text |Cite
|
Sign up to set email alerts
|

Balance between Polyoma Enhancing Activator 3 and Activator Protein 1 Regulates Helicobacter pylori–Stimulated Matrix Metalloproteinase 1 Expression

Abstract: Helicobacter pylori infection and elevated expression of tissue matrix metalloproteinase 1 (MMP-1) are both associated with gastric cancer. We investigated the regulation of MMP-1 expression during H. pylori infection. Real-time reverse transcription-PCR was used to examine mucosal MMP-1 mRNA levels in 55 patients with gastric cancers and 61 control patients. Increased MMP-1 mRNA levels in the gastric mucosa and epithelial cells were observed in H. pylori infections in which both the cag pathogenicity island (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 47 publications
4
39
0
1
Order By: Relevance
“…Furthermore, it was shown that Wnt5a signaling recruits JunD to the AP-1 site of the MMP-1 promoter region. These results were consistent with the previous observations Wnt5a and aggressiveness of prostate cancer H Yamamoto et al that the AP-1 site in the promoter region of the MMP-1 gene is critical for its transcriptional regulation (Angel et al, 1987) and that c-Jun and JunD bind to the AP-1 site (Doyle et al, 1997;Wu et al, 2006). In addition, knockdown of Fz2 and Ror2 reduced Wnt5a-dependent invasion and increment in MMP-1 mRNA.…”
Section: Mechanism By Which Wnt5a Promotes Aggressiveness Of Pcasupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, it was shown that Wnt5a signaling recruits JunD to the AP-1 site of the MMP-1 promoter region. These results were consistent with the previous observations Wnt5a and aggressiveness of prostate cancer H Yamamoto et al that the AP-1 site in the promoter region of the MMP-1 gene is critical for its transcriptional regulation (Angel et al, 1987) and that c-Jun and JunD bind to the AP-1 site (Doyle et al, 1997;Wu et al, 2006). In addition, knockdown of Fz2 and Ror2 reduced Wnt5a-dependent invasion and increment in MMP-1 mRNA.…”
Section: Mechanism By Which Wnt5a Promotes Aggressiveness Of Pcasupporting
confidence: 93%
“…In addition, Go¨6976 suppressed Wnt5a-dependent JNK activation (Figure 5c), suggesting Wnt5a activates JNK through PKD. c-Jun or JunD has been shown to bind to the AP-1 site in the promoter region of MMP-1 in MKN45 and U937 cells (Doyle et al, 1997;Wu et al, 2006). In a chromatin immunoprecipitation assay, MMP-1 promoter occupancy of JunD was decreased in DU145/Wnt5a knockdown cells compared with DU145/control cells (Figure 5d).…”
Section: Mechanism Of Wnt5a-induced Invasion By Pca Cellsmentioning
confidence: 94%
“…A 227-bp region upstream of the major transcriptional start site was found to drive higher reporter activity compared with the 128-bp, 449-bp, 2.3-kb, and 4.2-kb ones in monocytes (47). Stimulatory protein 1 and CCAAT/enhancer-binding protein binding sites, located at nucleotides À110 and À135, were shown to be critical for the CD14 expression (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of c-fos and c-jun mRNAs were measured by SYBR green I-based quantitative real time RT-PCR and, following normalization to glyceraldehyde-3-phosphate dehydrogenase mRNA, were expressed as -fold induction relative to the uninfected control, as previously described (23,24).…”
Section: Methodsmentioning
confidence: 99%